On The Oscillation of Second Order Non-Linear Differential Equations - Abdullah, Hishyar Kh. (International Journal of Applied Mathematical Research, 2013)
In this paper we are concerned with the oscillation of second order non-linear homogeneous differential equation. An example has been given to illustrate the results.